What is the ratio of two integrals involving sine with exponents of sqrt(2)?

  • MHB
  • Thread starter MountEvariste
  • Start date
  • Tags
    Integrals
In summary, "A tale of two integrals" is a mathematical concept that involves two different ways of solving integrals. The first integral, called the indefinite integral, involves finding the antiderivative of a function, while the second integral, called the definite integral, involves finding the area under a curve between two specified limits. The choice of integral depends on the problem at hand, and the concept is used in various real-world applications such as physics, engineering, and economics. There are also techniques and formulas that can be used to simplify the process of solving integrals, including integration by parts, substitution, and trigonometric identities.
  • #1
MountEvariste
87
0
$ \displaystyle I = \int_0^{\pi/2} \sin^{\sqrt{2}+1}{x}$ and $\displaystyle J = \int_0^{\pi/2} \sin^{\sqrt{2}-1}{x}$. Find $\displaystyle \frac{I}{J}.$
 
Last edited:
Mathematics news on Phys.org
  • #2
Recall the so-called Beta function defined by $$B(a,b) = \int_{0}^{1}t^{a-1}(1-t)^{b-1}\,dt.$$ Note that \begin{align*}\Gamma(a)\Gamma(b)&= \int_{0}^{\infty}e^{-u}u^{a-1}\,du\int_{0}^{\infty}e^{-v}v^{b-1}\,dv\\ &=\int_{0}^{\infty}\int_{0}^{\infty}e^{-u-v}u^{a-1}v^{b-1}\,du\,dv\end{align*} Setting $u = zt$ and $v=z(1-t)$, the change of variables theorem in 2-dimensions gives \begin{align*}\Gamma(a)\Gamma(b)&=\int_{0}^{\infty}e^{-z}z^{a+b-1}\,dz\int_{0}^{1}t^{a-1}(1-t)^{b-1}\,dt\\ &=\Gamma(a+b)B(a,b), \end{align*} from which we immediately obtain $$B(a,b) = \frac{\Gamma(a)\Gamma(b)}{\Gamma(a+b)}.$$ Using the substitution $t = \sin^{2}\theta$ in the definition of $B(a,b)$ above, we see that $$\frac{1}{2}B(a,b)=\int_{0}^{\pi/2}\sin^{2a-1}x\cos^{2b-1}x\,dx.$$ Hence, \begin{align*}\frac{I}{J}&=\frac{\frac{1}{2}B\left(1+\frac{1}{\sqrt{2}},\frac{1}{2}\right)}{\frac{1}{2}B\left(\frac{1}{\sqrt{2}},\frac{1}{2}\right)}.\end{align*} Using $B(a,b) = \dfrac{\Gamma(a)\Gamma(b)}{\Gamma(a+b)}$ and $\Gamma(z+1) = z\Gamma(z),$ the above becomes \begin{align*}\frac{I}{J} &= \frac{\Gamma\left(1+\frac{1}{\sqrt{2}} \right)\Gamma\left(\frac{1}{\sqrt{2}}+\frac{1}{2} \right)}{\Gamma\left(\frac{1}{\sqrt{2}} \right)\Gamma\left(1+\frac{1}{\sqrt{2}}+\frac{1}{2} \right)}\\ &= \frac{\frac{1}{\sqrt{2}}\Gamma\left(\frac{1}{\sqrt{2}} \right)\Gamma\left(\frac{1}{\sqrt{2}}+\frac{1}{2} \right)}{\left(\frac{1}{\sqrt{2}}+\frac{1}{2} \right)\Gamma\left(\frac{1}{\sqrt{2}}+\frac{1}{2} \right)\Gamma\left(\frac{1}{\sqrt{2}}\right)}\\ &=\frac{\sqrt{2}}{\sqrt{2}+1}\end{align*}
 
  • #3
Integrate by parts. $$\begin{aligned} I = \int_0^{\pi/2}\sin^{\sqrt2+1}x\,dx &= \int_0^{\pi/2}\sin x\sin^{\sqrt2}x\,dx \\ &= \left[-\cos x\sin^{\sqrt2}x\right]_0^{\pi/2} +\sqrt2 \int_0^{\pi/2}\cos^2x\sin^{\sqrt2-1}x\,dx \\ &= \sqrt2 \int_0^{\pi/2}(1 - \sin^2x)\sin^{\sqrt2-1}x\,dx = \sqrt2(J-I).\end{aligned}$$ Therefore $\dfrac IJ = \dfrac{\sqrt2}{\sqrt2+1}.$
 
  • #4
Nice solutions, GJA and Opalg.
 

Similar threads

Replies
4
Views
1K
Replies
1
Views
866
Replies
3
Views
2K
Replies
19
Views
2K
Replies
1
Views
834
Replies
2
Views
1K
Replies
4
Views
1K
Back
Top